2021
DOI: 10.2217/nnm-2020-0424
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Natural Product-Derived Carbon Dots in Cancer Biology

Abstract: Natural products have contributed conspicuously to the development of innovative nanomedicines. Hence, the interface between nanomaterial science and plant natural products may bestow comprehensive diagnostic and therapeutic strategies for tackling diseases such as cancer and neurological disorders. Natural product-derived carbon dots (NPdCDs) have revealed noteworthy attributes in the fields of cancer theranostics, microbial imaging, drug sensing and drug delivery. As plants consist of a cocktail of bioactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 169 publications
0
9
0
Order By: Relevance
“…282,518 Compared with traditional imaging agents, such as organic dyes and QDs (which sometimes exhibit low solubility and toxicities and small Stokes shifts), 0D CNMs-based imaging agents have excellent water solubility, biocompatibility, brightness, and photostability. 110,146,519,520 Bioimaging methods can be categorized as in vitro, in vivo, photoacoustic, radionuclide, and SR imaging. 521,522 In vitro imaging is usually performed on living cells, including cancer, B lymphocytes, macrophages, neutrophiles, granulocytes, and natural killer cells, mostly using an inverted fluorescence microscope, a laser confocal fluorescence microscope, and a transmission electron microscope, and HeLa, MG-63, A549, MCF-7, L929, HepG2, CCRF, THP-1, and HL-60 are the most widely used cell lines.…”
Section: In Vitro and In Vivomentioning
confidence: 99%
See 2 more Smart Citations
“…282,518 Compared with traditional imaging agents, such as organic dyes and QDs (which sometimes exhibit low solubility and toxicities and small Stokes shifts), 0D CNMs-based imaging agents have excellent water solubility, biocompatibility, brightness, and photostability. 110,146,519,520 Bioimaging methods can be categorized as in vitro, in vivo, photoacoustic, radionuclide, and SR imaging. 521,522 In vitro imaging is usually performed on living cells, including cancer, B lymphocytes, macrophages, neutrophiles, granulocytes, and natural killer cells, mostly using an inverted fluorescence microscope, a laser confocal fluorescence microscope, and a transmission electron microscope, and HeLa, MG-63, A549, MCF-7, L929, HepG2, CCRF, THP-1, and HL-60 are the most widely used cell lines.…”
Section: In Vitro and In Vivomentioning
confidence: 99%
“…The in-plane lattice spacing of CQDs usually varies from 0.15 to 0.25 nm . Because shrinking CQDs changes the state density from a band structure to discrete energy levels, CQDs are defined as “quantum”. , Frequently, the internal structure of CQDs is doped using diverse metals and nonmetals, while the CQDs surface can comprise various interesting functional groups. Therefore, the surface and internal structure both considerably contribute to diverse CQDs properties (Figure ).…”
Section: Structural Properties Of 0d Cnmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, CQDs obtained from medicinal plants have drawn attention in the last decade. Medicinal plant-based carbon quantum dots have shown excellent photostability, nontoxicity, high PL, and water solubility( Naik et al, 2021 ). However, no systematic study has so far been reported on the synthesis of medicinal plants-based CQDs.…”
Section: Medicinal Plant-based Carbon Quantum Dotsmentioning
confidence: 99%
“…The presence of various heteroatoms (N, P, S) in the phytomolecule causes self-functionalization during the carbonization process without using any additional passivating agents. Various parts of plant, such as fruits, leaves, stems, roots, bark, seeds, bulbs, and flowers, have been well explored as precursors for the synthesis of CDs [12]. Plant materials, such as pineapple fruit [13], Reishi Mushroom [14], Holy Basil leaves [15], Kalmegh leaves [16,17], Guar Gum [18], Hemp leaves [19], Japanese Apricot [10], Sapodilla fruits [20], Dragon fruits [21],…”
Section: Introductionmentioning
confidence: 99%